Measuring Firms’ Market Orientation Using Textual Analysis of 10‐K Filings - Andreou, Panayiotis; Harris, Terry; Philip, Dennis (My University, 2020)
Market-oriented firms are committed to understanding their customers’ evolving expectations and meeting their needs, while outwitting competitors, to achieve a sustainable competitive advantage and improve performance. This paper develops a measure for market orientation based on textual analysis of 10-K filings. It utilizes a bag-of-words method to identify relevant information from the management's disclosure that underpins the corporate traits measured by the MKTOR scale, a renowned survey instrument for measuring market orientation. Unlike previous studies that rely extensively on small-scale survey data to estimate market orientation, this novel method leverages instead on the use of big public archival data. We empirically establish strong construct validity for the measures of market orientation and its components, namely customer orientation and competitor orientation. Furthermore, our analyses demonstrate that firms’ performance is positively affected by market orientation and that this relationship is more pronounced in competitive environments. We contribute to the literature by developing an elegant measure of market orientation, which allows for conducting large-scale longitudinal analyses of its antecedents and consequences.
Keywords: Market orientation; Marketing capabilities; Customer ties